DNMT1 Level as Biomarker for Early Detection of Nasopharyngeal Carcinoma - Raudah Putri Syari; Zulham Yamamoto; Farhat; Sry Suryani Widjaja; Ririe Fachrina Malisie (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Introduction: Nasopharyngeal carcinoma (NPC) is a malignant disease often diagnosed at an advanced stage. Early detection of NPC is necessary to reduce morbidity and mortality of this disease. To date, early detection methods for NPC still have limitations, especially in terms of positive predictive value. Identification of DNA methylation abnormalities has been studied for its role as a marker for early detection of NPC. Objective: This review describes the potential of DNMT1, an enzyme involved in DNA methylation, as a biomarker for early detection of NPC. Methods: We conducted a literature search using PubMed and Google Scholar databases. The keywords used were